Creation of the ecological competence formation model of students of technical specialties and the study of its factors - Galtseva (Gal’tseva) O. V. Olga Valerievna; Plotnikova I. V. Inna Vasilievna; Nikitina A. I. Anastasiya Iljinichna; Rogachev A. A. Aleksandr Aleksandrovich (2017, 2017)
Title screen